2014
DOI: 10.1155/2014/638919
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Neovaginal Reconstruction Options in Male to Female Transsexuals

Abstract: Transsexualism is a complex condition in which the person experiences the inconsistency between the desired gender and their biological gender. Absence of the vagina is devastating in male to female transsexuals. Creation of the neovagina is the main surgical problem in these patients. Historically, beginnings of the neovaginal creation have their roots in the treatment of Mayer-Rokitansky syndrome and conditions such as cloacal anomalies, certain intersex disorders, vaginal malignancies, or severe vaginal tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 51 publications
0
64
0
2
Order By: Relevance
“…Using the part of the sigmoid colon, we can create a neovagina of adequate depth that will satisfy the patient. Due to the characteristics of the sigmoid colon, neova gina is self lubricating, has thicker walls and therefore is more resistant to trauma in comparison to the segment of the small intestine [22,23]. In the postoperative treat ment, neovagina does not require long term dilation, like in penile inversion vaginoplasty, except the dilatation of the introitus to prevent stenosis.…”
Section: Vaginoplasty Using Intestinal Segmentsmentioning
confidence: 99%
“…Using the part of the sigmoid colon, we can create a neovagina of adequate depth that will satisfy the patient. Due to the characteristics of the sigmoid colon, neova gina is self lubricating, has thicker walls and therefore is more resistant to trauma in comparison to the segment of the small intestine [22,23]. In the postoperative treat ment, neovagina does not require long term dilation, like in penile inversion vaginoplasty, except the dilatation of the introitus to prevent stenosis.…”
Section: Vaginoplasty Using Intestinal Segmentsmentioning
confidence: 99%
“…Trans seksualna osoba se oseća kao žena zarobljena u telu muškarca ili muškarac zarobljen u telu žene [58]. Te oso be često traže da im se hirurškim zahvatom promeni pol [59,60]. Beograd je trenutno jedan od vodećih svetskih centara za tu vrstu medicinskih zahvata.…”
Section: Medical Youthunclassified
“…The prevalence of male‐to‐female transsexuals in the general population is 1:7400 to 42,000 (Bizic et al, ), a threefold annual increase being reported as gender dysphoria becomes increasingly accepted in modern society (Colebunders et al, ). Sex reaffirmation surgery (SRS) is typically the last step in transitioning to the preferred gender after clinical diagnostic assessment, psychotherapy, and hormonal supplementation (Horbach et al, ).…”
Section: Introductionmentioning
confidence: 99%